Antimicrobic On KAFFIR LIME (Citrus hystrix) leaves against Bacillus cereus : KILL TEST METHOD - setiyo rini, chylen (Universitas Nahdlatul Ulama Surabaya, 2023)
Kaffir lime (Citrus hystrix) is a horticultural plant that is widely used as a natural flavor in various food and beverage products. The content in lime leaves is useful for health, including flavonoids, minerals, vitamin C, limonoids, and carotenoids. Bacillus cereus causes a diarrheal disease that attacks the intestines. This study aims to determine the kaffir lime leaf extract in inhibiting the growth of Bacillus cereus bacteria using the Time-Kill Test method. This study used the Minimum Inhibitory Concentration (MIC) and Time-Kill Test methods. The MIC results in kaffir lime leaf extract that can inhibit bacteria at 2 mg/mL, while the Time-Kill Test shows a death phase at 24 hours. Kaffir lime leaf extract has a bacteriostatic effect at 0, 4, 8, and 24 hours, while amoxicillin and the combination of amoxicillin and extract have a bacteriostatic effect at 4, 8, and 24 hours. Based on the results of the One Way ANOVA test with a 95% confidence level (p <0,05) showed a significant effect of kaffir lime leaf extract on the growth of Bacillus cereus.